Asignación de canon y sobre canon y su relación con el gasto de capital en municipalidades provinciales de la región Loreto periodo 2019 – 2022 - Rodriguez Salvador, Manuel Juan (2024)
The use of canon and over canon resources has always generated interest in the general population. Their use should be aimed at improving the conditions of the population's assets. The general purpose of the study is to determine the relationship between the allocation of canon and over canon. and capital expenditures in provincial municipalities of the Loreto region period 2019- 2022, for this purpose a quantitative observational methodology and a relational non-experimental design were used, which included as a population the expenditure records corresponding to capital expenditures, identifying those of infrastructure, acquisition of goods, pre-investment studies and technical files and the general budget item of non-financial assets. The study identified that During the period 2019-2022, the allocation of canon and over canon in the provincial municipalities of the region Loreto does not present a significant statistical relationship with capital expenditures, evidencing a diversity in investment priorities among municipalities. Despite the lack of correlation, it is notable that spending on infrastructure varies significantly between municipalities, being more pronounced in Alto Amazonas and Ramón Castilla. Expenses on the acquisition of assets, pre-investment studies and technical files also lack a significant statistical relationship, but notable patterns are observed, such as the notable investment in pre-investment studies in Loreto and Nauta, and the significant presence of technical files in Ramon Castilla. These observations highlight the importance of a decentralized approach in resource allocation and the need for strategic planning to optimize the use of funds and promote sustainable development in the region.